De Gaulle’s Legacy The Art of Power in France’s Fifth Republic - Nester, W.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
This book explores the following: What is the art of power? What is the art of French power? How did Charles de Gaulle understand and assert power, establishing the Fifth Republic and breaking centuries of political instability? How well or poorly have his successors wielded the art of French power to define, defend, or enhance French interests?
Keywords: Europe—Politics and government; Political science; Social sciences; European Politics; Political Science; Social Sciences, general